1989
DOI: 10.1042/bj2640805
|View full text |Cite
|
Sign up to set email alerts
|

Types of oligosaccharide sulphation, depending on mucus glycoprotein source, corpus or antral, in rat stomach

Abstract: Sulphated disaccharide and trisaccharide, possibly originating from the N-acetyl-lactosamine and fucosyl-N-acetyl-lactosamine sequences respectively, were detected in the corpus, especially as large oligosaccharides, but were present in the antrum in only very small amounts. The sulphated monosaccharide, however, most probably originating from 6-sulphated N-acetylglucosamine residues at non-reducing termini, was present in all oligosaccharide fractions in both the corpus and antrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…PGM34 extensively stained surface mucous cells in the fundic region, but only slightly stained pyloric gland cells (Figs 7Aa and 7Bb). In our previous study, we demonstrated that the 6‐sulfo H sequence is predominantly found on oligosaccharides of mucin present in the fundus region, whereas this sequence was only rarely found in the pyloric region [19]. Thus, this biochemical result is compatible with the immunohistochemical reactivity of PGM34 in the rat gastric section.…”
Section: Discussionsupporting
confidence: 77%
“…PGM34 extensively stained surface mucous cells in the fundic region, but only slightly stained pyloric gland cells (Figs 7Aa and 7Bb). In our previous study, we demonstrated that the 6‐sulfo H sequence is predominantly found on oligosaccharides of mucin present in the fundus region, whereas this sequence was only rarely found in the pyloric region [19]. Thus, this biochemical result is compatible with the immunohistochemical reactivity of PGM34 in the rat gastric section.…”
Section: Discussionsupporting
confidence: 77%
“…A GlcNAc6ST activity was also found to be present in the Golgi fraction of rat stomach; this enzyme acts on rat gastric mucin to form a product characterized as 6-SO 4 -GlcNAcβ1-3Galβ1-3GalNAc [8]. 6-Sulphated GlcNAc has been found in all regions of the rat stomach [8,70]. GlcNAc6ST activity is also present in human respiratory mucosa [4], rat sublingual gland [71], rat colon and cells derived from the colon [58,60,71].…”
Section: Glcnac6stsmentioning
confidence: 97%
“…Moreover, the CCK-B/gastrin receptor was shown to be involved in this mechanism (7). In the previous study, mucins obtained from the corpus and antrum of rat gastric mucosa were shown to differ in the chemical composition of their carbo hydrate moieties and subunit structures (12,13). These results and an immunohistochemical observation (14) strongly indicate that there are different types of mucus producing cells in the corpus and antrum, and the regula tory mechanism on mucin biosynthesis might differ be tween these two types of cells.…”
Section: Z-300 N-[3-[3-(piperidinomethyl)phenoxy]propyl]-2mentioning
confidence: 82%